The Effect of Acceptance and Commitment Therapy Islamic Approach On Self-Acceptance of Patients with Mental Disorder - Rasmawati, Rasmawati; Nur, Fauziah; Nurjannah, Sri (Jurnal Berita Ilmu Keperawatan, 2024)
Mental disorders have different manifestations and symptoms but are generally characterized by some combination of disturbances of thought, perception, emotion, behavior, and impaired relationships with other people. Severe mental disorders, including schizophrenia, are prone to stigma. Good self-acceptance has a robust negative correlation with stigma. This study examines the effect of Islamic acceptance and commitment therapy (ACT) on self-acceptance in patients with mental disorders. The research method is quantitative with a semi-experimental pre-post-test. Respondents in this study were 31 patients with mental disorders who were selected using a purposive sampling technique that met the criteria of being Muslim, awareness, and understanding of patients with mental disorders experienced in the good category, namely being aware of the disease experienced. The measuring instrument used in this study consisted of a demographic questionnaire and an Unconditional Self-Acceptance Questionnaire (USAQ). Results showed that ACT with Islamic approach significantly increased self-acceptance in a patient with mental disorders (P<0.001). ACT can be used as an effective intervention to increase self-acceptance in a patient with mental disorders.